PEMBINAAN PEGAWAI DALAM RANGKA MENINGKATKAN KINERJA PELAYANAN PUBLIK DI RUMAH SAKIT UMUM DAERAH PURI HUSADA KABUPATEN INDRAGIRI HILIR - jurnalmap map; Husna ÔÇÄ; Sri Mulyani (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
This study aims to describe the development of employee performance, especially career development of employees consisting of; (1) forms of career coaching; (2) obstacles in career coaching; (3) solutions made to overcome obstacles. The results of the study: 1) The forms of career guidance in RSUD Puri Husada include: providing general orientation on employee duties and functions, facilitating routine employee needs, socializing technical guidance to the executive level, involving employees in the technical guidance and training relevant to tupoksi, holding coordination meetings scope of internal and cross-sectoral (provincial) and planned promotion, lateral, and mutation processes. 2) Obstacles in employee career development, namely: limited funds in the addition of facilities and infrastructure. 3) Solutions made to overcome obstacles are: maintaining and utilizing existing facilities and infrastructure optimally, coordinating meetings to synchronize central government regulations and the work program of RSUD Puri Husada, socializing technical guidelines to the executive level through seminars and workshops, motivating employees practice and study independently, hold internal and cross-sectoral coordination meetings, disseminate work performance measurements based on SKP in order to assess objective performance, and send structural officials to follow DIKLATPIM. Keywords: career coaching